CENTRAL ASIA IN THE PRISM OF THE PHILOSOPHICAL APPROACH TO FOREIGN POLICY IN THE MODERN HISTORY OF UZBEKISTAN (CAHIERS MAGELLANES-NS, 2024)
The article substantiates that in the history of international relations, Central Asia has always played a key role in the geopolitical interests of great powers. The geographical features and natural resources of the region attracted, and continue to attract, at the present stage of development, the interests of leading actors in international relations. For these reasons, after the Central Asian countries gained political independence, the situation began to change. At the same time, one of the main initiators of philosophical thinking in considering issues of mutual understanding and interaction between the countries of the region is rightfully Uzbekistan.